Community paramedicine home visits: patient perceptions and experiences. (2nd June 2021) - Hughes, Stephen; Seenan, Christopher
Abstract : Background: Community paramedicine (CP) is an emerging model of community-based healthcare delivered around the world by paramedics with additional skills, education and training. There is a lack of qualitative research on patient perceptions and experiences of this phenomenon. Aims: The study aimed to explore patient perceptions and experiences of CP home visits delivered by specialist paramedics (SPs) in a Scottish urban general practice home-visit setting. Patient acceptance and CP primary-care strategic value were examined. Methods: An explorative qualitative study using purposive sampling, semi-structured interviews and thematic analysis. Findings: Five main themes were identified: provide a well-communicated, professional, knowledgeable and comprehensive home visit consultation; SP-patient relationship and continuity of care; acceptance of SP home visits in place of GP home visits; quicker response and an increased possibility of a home visit; and limitations of the SP role. Conclusion: Patient perceptions and experience of CP were positive, with patients accepting this model of care. Opportunities to improve healthcare, including better continuity or care and health monitoring, were found.